Penerapan Mesin Pengasap Ikan Bagi Nelayan di Sungai Suwi Muara Ancalong Kutai Timur - Rudy Agung Nugroho; Ari Susandy Sanjaya (LPPM UNINUS, 2018)
Community service program (Program Kemitraan Masyarakat or PKM) was done from July-September 2018 at Muara Ancalong, Kutai Timur Kalimantan. The aim of the program was to transfer Science and technology and assist the member of fisheries association to do fish smoking at Sungai Suwi, Muara Ancalong, Kutai Timur. By doing this program, the member of fisherman association will be having a soft skill and an experience in fish smoking. Further, this program can empower the member of Sungai suwi fisherman association to be an entrepreneurship, providing fish smoking product which has higher value than unsmoking fish. This program has been divided into two parts, Theory and practice with ratio 1:2. In theory, all team member of PKM has delivered a presentation regarding fish smoking technique. In the practice, the members of fisherman association directly built fish smoker and applied fish smoking . The outcome of the program was soft skill transfer technology, a module on how to smoke fish. In the future, this program can be implemented to gain the economic value for the members of fisherman association